Attitudes towards unethical behaviours in organizational settings: an empirical study - Wilks, Daniela Carvalho (ETHICS IN PROGRESS, 2011)
Employee misconduct is prevalent in organizations and may be counterproductive in social and material terms. It is thus important to better understand how misconduct is construed by employees and the factors that determine its ethical acceptability in specific cases. This study explores attitudes towards unethical and minor deviant behaviours by examining the degree of acquiescence towards them in a sample of employees. Based on previous studies it was hypothesized that both organizational commitment and job satisfaction would be negatively related to the acceptance of such behaviours in organizational settings. Results show that there is a relationship between the degree of acquiescence and organizational commitment and a more modest relationship with job satisfaction. They further indicate that organizational tenure impacts very significantly on the degree of acceptance. Although differences were found for age, neither gender nor organizational variables were found to be significant.